COVID-19: THE RISE OF CHINA AND SHIFT IN GLOBAL POWER STRUCTURE PERCEPTION OR REALITY - Najibullah; Ateeq Ahmed (International Journal of Contemporary Issues in Social Sciences, 2024)
The “Rise of China” became one of the core debating issues in international politics. Many expert opinions tend to argue that the power is in a shift from ‘’west’’ to ‘’east’’ under China as a great power. While the hegemony of U.S.A. is already challenged China, whose status has grown in the present century dramatically, took important positions on the global stage as a leader, exploiting the crisis of COVID-19 as it did during and after the 2008 financial crisis. The current scenarios and “decisive” policies of China suggest that it has placed itself as a world leader. Since 1990 the USA has enjoyed the monopoly being as the sole policeman in global politics. But during the last decade, the influence of the USA has decreased. China, on the other hand, has acquired most of the potential of hard power but of soft power also. The continuous global outreach under Xi in the last decade seemed to have confirmed the rising trend of China as a potential global power. The global standing of China under Xi and the American weakening position under Trump have been analyzed in this article. Though much of the scholars agreed on the rise of China this research argues whether a mere few indicators confirmed the rise of China as the next superpower or not. The main focus of the study is whether the rise of China as a global power to replace the US is a mere perception or reality by analyzing the debate about the rise of China.